Paul's letter to the Philippians in the light of disunity in the church - Peterlin, Davorin. (Novum Testamentum, Supplements, 1995)
This volume discusses the development of disunity in the Philippian church as the occasion for Paul's response in his letter. The first part of the book examines references and allusions to strife among the Philippians and tension between them and Paul. It demonstrates the pervasiveness of the theme of disunity in most sections of the letter. The second part correlates these findings with sections of the letter dealing with the Philippians' financial support for Paul. It treats such topics as Paul's attitude to money and the sociological composition of the church. The book's aim is to draw attention to social and non-theological aspects of the Philippian situation, and make a contribution to a more theological study of Philippians.